Electro-optical response of polymer-dispersed liquid crystals doped with γ-Fe2O3 nanoparticles. Issue 6 (3rd May 2022) - Meng, Xiangshen; Li, Jian; Lin, Yueqiang; Liu, Xiaodong; Li, Guoqing; Zhao, Jianwei; Miao, Yingning; Li, Wenjian; Ye, Wenjiang; Li, Decai; He, Zhenghong
ABSTRACT: In this paper, the microstructures of the dilute magnetic PDLC films, doped with low concentrations of γ-Fe2 O3 nanoparticles, have hardly changed, but their electric-optical responses have distinctly changed. The experimental results show that the threshold voltage and hysteresis decreased with the increasing concentration of γ-Fe2 O3 nanoparticles. Furthermore, at the relatively low concentration of γ-Fe2 O3 nanoparticles (samples (0) and (1) according to ϕm of 0 and 0.11%), the reciprocity of the rise time increased nonlinearly with the increasing square of the applied voltage. However, at the relatively high concentration of γ-Fe2 O3 nanoparticles (samples (2) according to ϕm  = 0.15%), the reciprocity of the rise time increased linearly with the square of the applied voltage. Moreover, the reciprocity of the decay time was independent of the applied voltage and decreased with increasing the concentration of γ-Fe2 O3 nanoparticles. These characteristics are due to the adsorption of free ions by γ-Fe2 O3 nanoparticles. As a result, the interfacial interaction between liquid crystal droplets and the polymer matrix decreased, and the effective electric field inside the liquid crystal droplets increased. Graphical abstract: uf0001